De (non-)ethiek van non-fictie. Over Ryszard Kapuściński en Frank Westerman - Zajas, Paweł (Academia Press, 2013)
As many authors have increasingly used ‘nonfiction’ to label their publications, the paper addresses issues related to this more and more common phenomenon. This comes as no surprise, for nonfiction is a lucrative genre, both for the authors and publishers. It is nevertheless important to bear in mind that nonfiction is not a limitless and endlessly flexible genre. In nonfiction, an underlying claim on the side of both the authors and publishers is that it offers a factual description of real- ity. Factual content as the basic component of nonfiction, is actually openly emphasized by the authors, publishers, bookseller and critics. In fact, however, many writers labeling their publications as nonfiction are not ready to abandon their fictional aspirations, thus breaking the pact established between them and the readers. This paper discusses instances of such a breach on the basis of the work of Ryszard Kapu􏰅ci􏰆ski en Frank Westerman.
Keywords: Frank Westerman, Ryszard Kapuściński, non-fiction